Cutting responses of additive manufactured Ti6Al4V with solid ceramic tool under dry high-speed milling processes. Issue 10 (July 2020) - Zhang, Heng; Dang, Jiaqiang; Ming, Weiwei; Xu, Xingwei; Chen, Ming; An, Qinglong
Abstract: Additive manufacturing (AM), an advanced manufacturing technology, has nowadays become increasingly popular in aerospace and biomedical fields since it provides the feasibility of producing complex-shaped Ti6Al4V components with faster speed and lower material waste. In order to achieve desirable shape dimensions and surface characteristics, finish machining operations are generally required. However, premature tool failure usually occurs with common carbide tools during the machining process while the performance of solid ceramic tool for AM Ti6Al4V alloy still remains unclear. To this end, the present work aims at studying the cutting responses of additive manufactured Ti6Al4V alloy with solid ceramic tool under dry high-speed milling processes. Various topics including cutting forces and cutting temperature fields as function of machining parameters were analysed. Furthermore, attention was also paid on the chip morphology, machined surface quality and tool wear mechanisms. The results indicate that the feed rate has greater impact on the magnitudes of cutting forces and temperature fields compared to the cutting speed. The continuous and free broken chips were generated during the milling process and the typically serrated morphology of chips were observed. The solid ceramic tool produces favorable machined surfaces under high-speed machining process apart from the tool edge marks. The mechanisms responsible for tool wear were determined to be micro chipping and chip adhesion owing to the mechanical and thermal loading.